Denture Wearing and Malnutrition Risk Among Community-Dwelling Older Adults - Su, Ya (Nutrients, 2020)
Most studies have associated denture wearing with a higher risk of malnutrition and lower nutritional intake in the elderly. As the effect of wearing dentures remains debatable, the aim of this study was to determine if older adults wearing dentures have a higher risk of malnutrition. We recruited 294 Japanese community-dwelling adults aged ≥65 years from two elderly welfare centers in Sapporo. The Mini Nutritional Assessment-Short Form (MNA-SF) was used to assess their nutritional status. Their demographic characteristics, eating habits, and health status were assessed using a questionnaire. Moreover, salt-impregnated taste paper and bioelectrical impedance analysis were used to obtain salt taste sensitivity and body composition (body mass index and protein mass). The mean age of older adults was 75.8 ± 5.8 years and 71.1% were women. We found that 74.1% of the older adults wore dentures. The proportion of the whole population with a risk of malnutrition was 23.5%. Multivariate analysis revealed that partial denture wearing could be protective against the risk of malnutrition. In this study, we found more partial denture wearers with normal nutritional conditions and cooking by themselves than non-denture-wearing older adults. Furthermore, complete denture wearers were eating significantly less meats or fish every day. This study suggests that using partial dentures to replace the lost teeth to meet the dietary needs of the elderly is critical to maintaining a healthy nutritional status. Moreover, it also indicates the importance of providing education to older adults who wear complete dentures.